2006
DOI: 10.1111/j.1365-2222.2006.02394.x
|View full text |Cite
|
Sign up to set email alerts
|

Repair of the injury to respiratory epithelial cells characteristic of asthma is stimulated by Allomyrina dichotoma agglutinin specific serum glycoproteins

Abstract: These results indicate that following mechanical injury to the epithelium, serum glycoproteins, not only provide a protective barrier, but also are involved in the initiation of wound closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…6B). Previous studies had localized fetuin A labeling to cells adjacent to scrape zones of wounded monolayer cultures (45). However, its co-localization with membrane repair proteins was not investigated.…”
Section: Resultsmentioning
confidence: 99%
“…6B). Previous studies had localized fetuin A labeling to cells adjacent to scrape zones of wounded monolayer cultures (45). However, its co-localization with membrane repair proteins was not investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Monolayers were washed with phosphate-buffered saline (PBS) followed by the addition of DMEM ϩ 10% FBS. After 18 h in culture, protein collection and lectin precipitation was carried out as previously described (40). Biotinylated lectin (20 g of CPA or VVA, EY Laboratories) was added to the supernatant and incubated overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…In both studies, the same global inhibitor of N-glycosylation was used, but the specific cell surface glycoproteins that were altered by this inhibition were not identified. Further work by Adam et al (1) has shown that in culture, functional carbohydrate structures can be identified on the surface of cells by lectin histochemistry and wound closure inhibition (40).…”
mentioning
confidence: 98%
“…In this study the authors demonstrated that blocking glucose, mannose, and glucosamine sites on corneal epithelial cell surfaces and/ or the epithelial basement membrane reversibly slows or inhibits epithelial migration [78]. Using the same culture model of bronchial epithelial repair, Patchell et al has demonstrated that following mechanical wounding of intact monolayers, the lectins Allomyrina dichotoma (AlloA) and chick pea agglutinin (CPA) differentially stain human airway epithelial cells in damaged areas relative to the staining of intact epithelial monolayers [89]. While AlloA positive staining cells are those that appear to be migrating from areas distant to the wound and accumulating in the wound, CPA positive staining cells are restricted to the leading edge of the wound.…”
Section: Role Of Cell Surface Glycoconjugates In Epithelial Repairmentioning
confidence: 99%